If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) + 6 = 2(x + -5) Reorder the terms: 4(-5 + x) + 6 = 2(x + -5) (-5 * 4 + x * 4) + 6 = 2(x + -5) (-20 + 4x) + 6 = 2(x + -5) Reorder the terms: -20 + 6 + 4x = 2(x + -5) Combine like terms: -20 + 6 = -14 -14 + 4x = 2(x + -5) Reorder the terms: -14 + 4x = 2(-5 + x) -14 + 4x = (-5 * 2 + x * 2) -14 + 4x = (-10 + 2x) Solving -14 + 4x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -14 + 4x + -2x = -10 + 2x + -2x Combine like terms: 4x + -2x = 2x -14 + 2x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 -14 + 2x = -10 + 0 -14 + 2x = -10 Add '14' to each side of the equation. -14 + 14 + 2x = -10 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = -10 + 14 2x = -10 + 14 Combine like terms: -10 + 14 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 5(2x-3)=2(x-2)+5 | | 2X^2-11X-6=0 | | 10y-13=3y+8 | | -3z=12 | | 7(4x+6)=-126 | | 2x*2+21x-11=0 | | f=3x^2-26x+48 | | 8n+5=6n-3 | | 3a+4-a+2=10 | | g(x)=7x-14 | | 6+7y=48 | | .8333333333+.2x=.666666667 | | 13+11x=68 | | 2x+9x=11x | | 6x^2-16x+7=0 | | -4.3=0.7-5y | | 6x-2=3(x+1)+1 | | 4x-90=-6x+40 | | 4n^2-17n+4= | | 2d-7=11d+26 | | 8x+16=9x+9 | | C(m)=0.15m+0.95 | | 6y-4=y+6 | | 4(3x-2)=2(6x+9) | | P-17=67 | | X+-5x+3=-5 | | .16(x-36)=.83 | | 7x-4x=4x-2 | | 10+3j=31 | | 2.3y+1.2=2.12whatisy | | 4x(2x-1)(3x-5)=0 | | 7x+9-2x=11-12x-13 |